3D Printed Sugar‐Sensing Hydrogels. Issue 9 (24th February 2020) - Bruen, Danielle; Delaney, Colm; Chung, Johnson; Ruberu, Kalani; Wallace, Gordon G.; Diamond, Dermot; Florea, Larisa
Abstract: The ability of boronic acids (BAs) to reversibly bind diols, such as sugars, has been widely studied in recent years. In solution, through the incorporation of additional fluorophores, the BA–sugar interaction can be monitored by changes in fluorescence. Ultimately, a practical realization of this technology requires a transition from solution‐based methodologies. Herein, the first example of 3D‐printed sugar‐sensing hydrogels, achieved through the incorporation of a BA–fluorophore pair in a gelatin methacrylamide‐based matrix is presented. Through optimization of monomeric cocktails, it is possible to use extrusion printing to generate structured porous hydrogels which show a measurable and reproducible linear fluorescence response to glucose and fructose up to 100 mm . Abstract : UV‐assisted extrusion printing of a boronic acid–fluorophore pair within a gelatin‐methacrylamide matrix results in stable hydrogel lattices, which allow for the determination of sugar concentration via easily monitored changes in fluorescence.